Assessing Mental Health of Women Living in Karachi During the Covid-19 Pandemic - Asim, Shabnam Shamim; Ghani, Samrah; Ahmed, Maheen; Asim, Anushae; Qureshi, Afzal Fatima Karim (Frontiers in Global Women's Health, 2021)
Introduction: Women are more susceptible to mental health disorders and have been reported to experience higher levels of depression and anxiety during previous large-scale disease outbreaks. Stressful events like the COVID-19 pandemic can add extra burdens to women’s already multifaceted lives. Keeping the gender implications of COVID-19 in mind can assist health care workers to offer more effective management. In our study, we aimed to assess the impact of COVID-19 on the mental health of women in Karachi, Pakistan and investigate the possible risk factors. Methods: An online questionnaire was distributed to women on social media platforms in the month of June 2020. The questionnaire had two self-assessment scales, Patient Health Questionnaire (PHQ-9) scale which measures the symptoms of depression and General Anxiety Disorder (GAD-7) scale which measures anxiety. Results: 393 individuals completed the questionnaire with the mean age calculated to be 27.6 ± 11.7 years. Age, education, marital status, number of children, financial issues, employment status, smoking, comorbidities and mental illnesses were significantly associated with participants’ mean anxiety and depression scores. The depression scores were generally higher compared to anxiety scores in each category. As the age increased, their scores decreased, with women aged 18-30 having a significantly higher mean depression and anxiety scores compared to women who were above 50. Severe anxiety was identified in 21.9% women and severe depression was noted in 17.8% women. A frightening number of 148 (37.7%) was found of women who had self-destructive thoughts at one time or another. Out of these women, surprisingly 97 (65.5%) individuals were not previously diagnosed with any mental illnesses. Discussion: This study supports the existing literature regarding the disturbed psychological state of women close to the peak of the COVID-19 pandemic. We noted increased percentage of depressive women as compared to studies conducted before the COVID-19 era. This raises concern especially with our thought provoking finding of self-harm or suicidal thoughts among women. Most of our female population is also seen to be anxious. This study highlights the importance for help and support groups of mental health to effectively reach women during this period of social isolation.